2019
DOI: 10.1186/s12909-019-1859-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of test anxiety among medical students in Addis Ababa Ethiopia

Abstract: BackgroundWorldwide, problematic test anxiety is a common health problem among medical students. The magnitude of problematic test anxiety ranges from 25 to 40% in undergraduate medical students and has a detrimental effect on academic achievement and success of students. However, data on the prevalence of test anxiety among medical students is limited. Thus, the study aimed to assess the prevalence and associated factors of test anxiety among medical students.MethodsIn this cross-sectional study, a stratified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 32 publications
4
57
1
13
Order By: Relevance
“…Regarding the response process (R), the analyses revealed a medium level of anxiety among the participants irrespective of gender, which is in line with the available evidence (Lowe, 2019;Nunez-Pena et al, 2016;Sung et al, 2016;Tsegay et al, 2019). However, as noted before, given that male participants significantly outnumbered their female peers, any gender-related findings need to be interpreted with caution.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Regarding the response process (R), the analyses revealed a medium level of anxiety among the participants irrespective of gender, which is in line with the available evidence (Lowe, 2019;Nunez-Pena et al, 2016;Sung et al, 2016;Tsegay et al, 2019). However, as noted before, given that male participants significantly outnumbered their female peers, any gender-related findings need to be interpreted with caution.…”
Section: Discussionsupporting
confidence: 85%
“…High levels of test anxiety tend to interfere with academic performance, potentially resulting in procrastinate on assignments, or even difficulties in learning due to failures in information processing or difficulties in organizing and retrieving information, ultimately jeopardizing students' mental health (Cassady, 2004;Custer, 2018;Jalilian et al, 2016;Malloy, 2016;Naveh-Benjamin et al, 1987). According to the available data, approximately 18% to 50% of students experience some degree of test anxiety (Ahmad et al, 2018;Bhuvaneswari, 2020;Marcue & Gonzalez, 2017;Thomas et al, 2017;Tsegay et al, 2019). However, it is particularly worrisome that nearly 7−25% of students suffer very high levels of test anxiety (Bhuvaneswari, 2020;Thomas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Paying attention to the issue of anxiety in medical students requires more care because of the important consequences it can have (21,22). (31). Therefore, the amount of test anxiety that causes the problem, which the results of studies indicate is common among medical students, should be given more attention.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a relation between test anxiety and dysfunction (38). Problematic test anxiety rates of 25 to 40% in undergraduate medical students can have devastating effects on academic performance and student achievement (31). Anxiety can lead to mental distress and negatively affect students' cognitive performance and learning (45).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found the same association of female gender and a higher level of GA among pharmacy and non-pharmacy students. 1,[25][26][27] The second factor evaluated was physical activity. Similar to the Feltz-Cornelis and colleagues' study and the study by Xiang and colleagues, our data suggested an association between low physical activity and low-clinical GA (Table 2).…”
Section: Discussionmentioning
confidence: 99%